2022
DOI: 10.3390/nu14224911
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Patterns and Obesity in Chinese Adults: A Systematic Review and Meta-Analysis

Abstract: Certain dietary patterns are associated with an increased risk of obesity and its comorbidities. However, these associations vary across populations. The prevalence of obesity has been rising amid a drastic nutrition transition in China during the country’s rapid economic growth. This systematic review and meta-analysis were conducted to summarize how dietary patterns are associated with obesity in the Chinese population. We searched for articles from 1 January 2000 to 1 February 2022 in PubMed, Cumulative Ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…Recognizing the classification of Chinese diets is essential, particularly if these characteristics are associated with non-communicable diseases. In a Chinese meta-analysis, the traditional Chinese dietary pattern, including starchy foods (i.e., rice, wheat, and tubers), vegetables, and high-protein foods (i.e., pork) was associated with a lower risk of overweight/obesity [ 35 ]. Although Chinese dietary styles have been adapted in Japan, the presence of Chinese diets within Japanese food culture should be acknowledged.…”
Section: Discussionmentioning
confidence: 99%
“…Recognizing the classification of Chinese diets is essential, particularly if these characteristics are associated with non-communicable diseases. In a Chinese meta-analysis, the traditional Chinese dietary pattern, including starchy foods (i.e., rice, wheat, and tubers), vegetables, and high-protein foods (i.e., pork) was associated with a lower risk of overweight/obesity [ 35 ]. Although Chinese dietary styles have been adapted in Japan, the presence of Chinese diets within Japanese food culture should be acknowledged.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the dietary intake of hemodialysis patients in the past month, a Food Frequency Questionnaire was utilized, following the Chinese Dietary Guidelines (2022). [ 10 ] The Food Frequency Questionnaire consisted of inquiries regarding the frequency of consumption for various food groups, including grains, potatoes, vegetables, fruits, animal-based foods, milk and dairy products, soybeans, and nuts. Participants were requested to report both the frequency and quantity of consumption for each food group.…”
Section: Methodsmentioning
confidence: 99%
“…64 However, our study showed a significant association among individuals without depression/anxiety. Third, individuals practicing the TSCD are leaner, 30,65,66 and subsequently their risk of PMDs is lower. 8 Nevertheless, BMI has been thoroughly adjusted in our analysis and cannot explain our findings.…”
Section: Papermentioning
confidence: 99%